Nurses’ experiences of learning tasks in career development: A phenomenological study - Kabak, Edison (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Learning assignments are an important strategy in increasing the capacity and career path of nurses, but this process often leads to role changes, academic pressures, and professional identity dynamics that are not fully understood. Purpose: To examine the meaning of the experience of nurses undergoing learning tasks in career development. Method: A phenomenological approach by involving twelve nurses who had completed a learning task. Data was collected through in-depth interviews and thematically analyzed to uncover consistent patterns of experiences among participants. Results: Five themes emerged: competency and career development through learning tasks, institutional and mentor support, emotional responses to academic pressure and dual roles, evolving professional values and identity, and work–family–study balance challenges. Overall, learning tasks support both technical growth and reflective professional maturity. Conclusion: Assignments are transformative experiences that provide career development opportunities, but require policy support and ongoing mentoring for nurses to be able to go through this process optimally.